Blogging for Sustainability: The Intermediary Role of Personal Green Blogs in Promoting Sustainability. Issue 5 (4th July 2018) - Joosse, Sofie; Brydges, Taylor
ABSTRACT: The rise of social media radically broadens the sources and platforms used for environmental communication. Especially personal green blogs are worthy of study as they are spaces of everyday cultural politics through which people make sense of sustainability issues, and because they entail a radical break from conventional media in terms of legitimacy, form, and content of environmental communication processes. This paper studies the representation of sustainability on personal green blogs, and the communication processes through which these representations are constructed. It does so through a qualitative study of Swedish-language blogs. We study three blogs in-depth: a living experiment blog on sustainable food practices; a lifestyle blog centered around green family life; and a blog about consuming green beauty products. The analysis shows that all three blogs translate the complex landscape of sustainability to individual everyday practices. Yet, what these sustainability practices entail differs considerably between the blogs, ranging from a-political and doable lifestyle choices to an onset to radical redefining of consumption. Also, the communication processes on the blogs differ in quality and quantity. The paper uses these insights to reflect on the debates about how environmental communication is shaped by blogging and social media practices.